1982
DOI: 10.1063/1.330628
|View full text |Cite
|
Sign up to set email alerts
|

Electrical derivative characteristics of InGaAsP buried heterostructure lasers

Abstract: Results of a study of the electrical derivative characteristics of InGaAsP buried heterostructure lasers are presented. By considering current-leakage paths and electrical contact nonlinearities, an equivalent circuit model appropriate to the buried heterostructure laser has been developed. Solutions for the theoretical electrical derivatives of series-parallel-reducible networks have been obtained and applied to the equivalent circuit model of the buried heterostructure laser. Comparison of experimentally mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In this paper, a typical circuit model [1] used in IdV/dI method is employed to interpret experimental results mentioned in Section 2. The typical equivalent circuit model is presented in Fig.6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, a typical circuit model [1] used in IdV/dI method is employed to interpret experimental results mentioned in Section 2. The typical equivalent circuit model is presented in Fig.6.…”
Section: Discussionmentioning
confidence: 99%
“…Voltage-current (V-I) is a general indicator to estimate the reliability nondestructively, but they are too insensitive to some microscopic processes. Some references have reported that electrical derivative (IdV/dI-I) is more sensitive than V-I [1][2]. However, they are usually not enough to signal an impending breakdown, even this breakdown occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The increased separation also increases both the minority carrier leakage over the double-heterostructure barrier 16 and the shunt current around a buried active layer. 6,28 Each of these four contributions to the increase in i may have its own temperature dependence. Thus, except for fortunate cases where a single response dominates, any macroscopic black-box activation energy necessarily reflects multiple microscopic processes.…”
Section: Comparison Of Activation and Extrapolation Methodsmentioning
confidence: 99%
“…For GaAs-based LED chips, many papers have described a useful simplified electrical circuit or proposed analytic modelling deduced from electrical measurements, where the active zone is generally represented by an ideal diode D hj for a radiative phenomenon and D ho for a non-radiative phenomenon in addition to an overall linear resistance (R s ) 24,[27][28][29] . The value of R s sums the contribution of the contact resistance between the thin metal layer and the semiconductor GaAs N + and P + -doped, and the bulk resistance of the GaAs N + and P + -doped layers 30 . For instance, first-order derivative calculations from I (V ) curves can also reveal the presence of additional series resistance, either linear or nonlinear, the effect of non-ohmic contact and the temperature dependence of the equivalent circuit model.…”
Section: Electrical Characterizationsmentioning
confidence: 99%